Design and Performance Analysis of OFFGRID PV mini-grid systemsSimulation PVSYST in Sukabumi, West Java, Indonesia - Marina Artiyasa; Muhammad Natsir; Bahadir Ozsut (Nusa Putra University, 2023)
Indonesia is a tropical country whose sunlight always shines because it is at the equator, but unfortunately its abundant potential is underutilized, therefore here we want to make a 5MW PLTS research which includes PLTS for small industries using PVsyst simulation, located in Cibolang Kaler, Kab Sukabumi, West Java. With PVsyst we can get an idea of how much it will cost, then meteo according to the location, the results of the energy obtained, loss diagrams of various kinds of losses, as well as various other parameters. From the results obtained to get PLTS 5 MW (5000000) W, with panels we need as many as 560 solar panels with a size of 415W, Li Ion batteries with a size of 180Ah as many as 4293 pieces and an overall cost of 43 billion more and will return the capital in 14.8 year